Narrative Literature Review : Efektivitas Penggunaan Anggaran Operasional dalam Meningkatkan Kinerja Pelayanan Rumah Sakit (Lembaga Pengembangan Kinerja Dosen, 2025)
Hospitals, as both public service institutions and business entities, are required to manage their finances effectively to maintain service quality and financial sustainability. Operational budgets play a vital role in supporting service delivery, encompassing the availability of medical staff, medicines, and infrastructure, as well as facility maintenance. This study aims to provide an in-depth review of the effectiveness of operational budget utilization in relation to hospital service performance. The method employed is a narrative literature review, drawing upon eight scholarly articles published in the last five years that are relevant to the research topic. The findings indicate that effective operational budgeting is closely related to performance indicators, such as Bed Occupancy Rate, Average Length of Stay, Turnover Interval, patient visits, and patient satisfaction. Proper budget management not only enhances efficiency but also positively impacts staff motivation, patient safety, and hospital financial sustainability. Conversely, weaknesses in budget planning and execution may lead to decreased service quality and patient dissatisfaction. The implications of this study emphasize the need for performance-based budget governance that is integrated with service indicators, enabling hospitals to achieve a balance between cost efficiency, service quality, and organizational sustainability.